The Effect of School Year and Summer Break in Health-Related Cardiorespiratory Fitness: A 2-Year Longitudinal Analysis - De Moraes-Ferrari, G (Routledge, 2022)
This study aimed to assess the trends of health-related cardiorespiratory fitness (CRF) during two school years with a 3-month summer break in children and adolescents. A 2-year longitudinal study, including 440 6th to 8th graders (218 boys), mean age 12.3 years, was conducted. The Progressive Aerobic Cardiovascular Endurance Run (PACER) was used to assess CRF. Physical activity was measured using accelerometers. Repeated measures linear models were used to analyses differences and trends in VO2peak and health-related CRF. Overall differences between time-point VO2peak were significant for both boys (p<0.001) and girls (p=0.003). Pairwise comparisons showed that VO2peak improved from the beginning to the end of the same school year for boys (school-year 1: 1.53 ml/kg/min, 95%CI=0.98, 2.09; school-year 2: 1.81 ml/kg/min, 95%CI=1.28, 2.34) and girls (school-year 1: 0.85 ml/kg/min, 95%CI=0.43, 1.27; school-year 2: 1.05 ml/kg/min, 95%CI=0.73, 1.36), while, differences in CRF during summer break were not significant. However, significance was only maintained for girls when performing monthly adjusted analysis. Improvements in CRF were observed during school year and remained unchanged during summer break. These findings provide relevant information for the health education community, suggesting the need for additional efforts to counteract the summer break effects on CRF, especially for girls.                      . © 2022 Informa UK Limited, trading as Taylor & Francis Group.